2018
DOI: 10.1002/lary.27394
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin‐Releasing Peptide Is Involved in the Establishment of Allergic Rhinitis in Mice

Abstract: NA. Laryngoscope, E377-E384, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…Furthermore, interestingly, it has been reported that a GRPR antagonist resulted in a greater antiinflammatory effect than corticosteroids 32) . Our findings of reduced instances of sneezing and nasal rubbing following the administration of a GRPR antagonist in AR mice were consistent with these reports 29) . Furthermore, RC-3095 was especially effective at suppressing the sneezing induced by histamine in the 20-min period following administration; however, its effects were not very robust 29) .…”
Section: Gastrin-releasing Peptidessupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, interestingly, it has been reported that a GRPR antagonist resulted in a greater antiinflammatory effect than corticosteroids 32) . Our findings of reduced instances of sneezing and nasal rubbing following the administration of a GRPR antagonist in AR mice were consistent with these reports 29) . Furthermore, RC-3095 was especially effective at suppressing the sneezing induced by histamine in the 20-min period following administration; however, its effects were not very robust 29) .…”
Section: Gastrin-releasing Peptidessupporting
confidence: 92%
“…Our findings of reduced instances of sneezing and nasal rubbing following the administration of a GRPR antagonist in AR mice were consistent with these reports 29) . Furthermore, RC-3095 was especially effective at suppressing the sneezing induced by histamine in the 20-min period following administration; however, its effects were not very robust 29) . This suggests that RC-3095 does not suppress the mechanism underlying the symptoms caused by histamine (free histamine, or histamine that was directly administered to mice); instead, it suggests that RC-3095 acts on either histamine release by mast cells/basophils or a reaction upstream of this release 29) .…”
Section: Gastrin-releasing Peptidessupporting
confidence: 92%
See 3 more Smart Citations